2020
DOI: 10.3390/ijms21145019
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1 and D2 Inhibit Transient Receptor Potential Vanilloid 1 and Ankyrin 1 Ion Channel Activation on Sensory Neurons via Lipid Raft Modification

Abstract: Transient Receptor Potential Vanilloid 1 and Ankyrin 1 (TRPV1, TRPA1) cation channels are expressed in nociceptive primary sensory neurons and regulate nociceptor and inflammatory functions. Resolvins are endogenous lipid mediators. Resolvin D1 (RvD1) is described as a selective inhibitor of TRPA1-related postoperative and inflammatory pain in mice acting on the G protein-coupled receptor DRV1/GPR32. Resolvin D2 (RvD2) is a very potent TRPV1 and TRPA1 inhibitor in DRG neurons, and decreases inflammatory pain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…181 Meanwhile, RvD1 and RvD3 exert their bioactions through binding to ALX/FPR2 and DRV1/GPR32, respectively, whereas RvD2 and RvD5 activate their DRV2/GPR18 and DRV1/GPR32 receptors, respectively. 178,182,183 Of interest, the activation of the RvE1-ERV1/ ChemR23 axis has been shown to promote the apoptosis and macrophage-mediated phagocytosis of neutrophils, while reducing the production of pro-inflammatory cytokines. [184][185][186] Recently, we also found that RvD P 5 inhibited the infiltration of neutrophils and promoted the phagocytic function of macrophages through the ALX/FPR2 receptor.…”
Section: Inflammation Resolutionmentioning
confidence: 99%
“…181 Meanwhile, RvD1 and RvD3 exert their bioactions through binding to ALX/FPR2 and DRV1/GPR32, respectively, whereas RvD2 and RvD5 activate their DRV2/GPR18 and DRV1/GPR32 receptors, respectively. 178,182,183 Of interest, the activation of the RvE1-ERV1/ ChemR23 axis has been shown to promote the apoptosis and macrophage-mediated phagocytosis of neutrophils, while reducing the production of pro-inflammatory cytokines. [184][185][186] Recently, we also found that RvD P 5 inhibited the infiltration of neutrophils and promoted the phagocytic function of macrophages through the ALX/FPR2 receptor.…”
Section: Inflammation Resolutionmentioning
confidence: 99%
“…Numerous agonists of GPR18 have been proposed, including abnormal cannabidiol (Abn-CBD, 74 ), Δ 9 -tetrahydrocannabinol ( 75 ), O-1918 ( 76 ), N -arachidonoyl glycine ( 77 ), resolvin D1 ( 78 ), and resolvin D2 ( 79 ) (Figure ). , These compounds are cannabinoid related, suggesting that it might be appropriate to classify GPR18 as a cannabinoid receptor together with CB1 and CB2. N -Arachidonoyl glycine ( 77 ) is the putative endogenous ligand of GPR18 .…”
Section: Approaches To Develop Safer Ligands For New Pain Targetsmentioning
confidence: 99%
“…117 Numerous agonists of GPR18 have been proposed, including abnormal cannabidiol 12). 118,119 These compounds are cannabinoid related, suggesting that it might be appropriate to classify GPR18 as a cannabinoid receptor together with CB1 and CB2. N-Arachidonoyl glycine (77) is the putative endogenous ligand of GPR18.…”
Section: Nonsteroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%
“…For instance, MaR1 reduces TRPV1 and Nav1.8 mRNA expression, and capsaicin neuronal activation (Fattori et al, 2019). RvE1 reduces TNF‐α‐induced excitatory postsynaptic current frequency in spinal cord neurons (Xu et al, 2010) while RvD2 reduces TRPV1 sensitization (Payrits et al, 2020; Perna et al, 2020).…”
Section: Discussionmentioning
confidence: 99%